Analysis of the Characteristics of Chronic Energy Deficiency in Pregnant Women during the Covid 19 Pandemic - Hardianti Mukkadas; I Made Cristian B; Wa Ode Salma (STIKes Hang Tuah Pekanbaru, 2021)
Pregnant women who experience chronic energy deficiency (KEK) tend to give birth to LBW babies and have a greater risk of death. Objective: This study was to analyze the factors associated with the incidence of KEK in pregnant women. Methods: The study was conducted for 2 months, in 2020 at Anggaberi Health Center and Soropia Health Center in Konawe district. Design: cross sectional, quantitative data collection and secondary data. The research sample was pregnant women who were registered in the maternal cohort data, which were taken randomly as many as 115 people. Univariate data analysis was carried out descriptively to see the distribution of the values ​​of the causal factors, bivariate analysis was carried out to analyze the relationship between the causal factors and the incidence of KEK through statistics, namely Chi-square test and cross tabulation with a significance value of 0.05. The results of the study found that the factors associated with the incidence of KEK were age (p-value = 0.000), education level (p-value = 0.000), employment status (p-value = 0.000), and pregnancy weight (p-value = 0.000 ). The incidence of KEK is more likely in mothers who have characteristics such as age < 20 years and > 35 years, low education, not working and low pregnant weight. Therefore, it is hoped that an increase in food security at the family level can be socialized through providing information to preconception women through counseling, flip-charts and posters.